Flexural behavior of seawater-mixed steel fiber reinforced concrete exposed to simulated marine environments. (10th April 2023) - Zhang, Shun; Gao, Danying; Zhu, Haitang; Chen, Lianxin; He, Zhenhao; Yang, Lin
Highlights: Prepare a kind of steel fiber reinforced concrete (SFRC) with sea water. Flexural properties of different types of concrete were investigated. DIC and AE techniques were used to verify the results. Degradation mechanism of seawater-mixed SFRC in different environments was analyzed. Abstract: The application of seawater-mixed concrete can effectively reduce the use of the freshwater for concrete production. Moreover, the steel fibers added into concrete matrix can improve its mechanical properties. This paper investigated the flexural behavior of seawater-mixed steel fiber reinforced concrete (SFRC) exposed to simulated marine environments for 1 year using four-point bending tests. The influences of the type of mixing water, the type of exposure environment and the degree of pre-cracking damage on the flexural performance of seawater-mixed SFRC were mainly studied. Meanwhile, the acoustic emission (AE) and digital image correlation (DIC) techniques were utilized to monitor the characteristics of the damage in concrete and the evolution of the cracks on the concrete surface. Results showed that there were many rust spots on the surface of seawater-mixed SFRC specimens after 1 year of chloride attack, especially for cracked specimens, and the moderate steel fiber corrosion was only found near the cracks of the cracked SFRC specimens with an average crack width of 0.46 mm. The seawater-mixed SFRC specimens and freshwater-mixed SFRC specimens exposed to 7% NaCl solution for 1 year showed slight decreases in their flexural strength and toughness compared with unexposed specimens, respectively. However, the seawater-mixed SFRC exposed to freshwater environments for 1 year under wet-dry cycle treatments and the cracked seawater-mixed SFRC with an average crack width of 0.46 mm exposed to chloride environments for 1 year showed obvious deterioration, respectively. It was noted from AE and DIC results that the AE counts of different types of concrete specimens indicated easily distinguishable change characteristics and the maximum strain at the main crack of cracked seawater-mixed SFRC was larger due to serious damage after exposure for 1 year. The results of AE and DIC had a good correspondence with the variation trend of load–deflection curves.